The Competitiveness of the Bottled Natural Water and Purified Drinking Water Enterprises in Vietnam: Input To Operational Plan - Quang Khoi, Le (British Journal of Marketing Studies, 2019)
This study aims to explore the key factors affect the competitiveness of the bottled natural mineral water and purified drinking water enterprises in Vietnam. The researcher surveyed 340 members of board of directors at bottled natural mineral water, purified drinking water enterprises in four big cities of Vietnam. Sample was divided as follows: Ho Chi Minh City has 200 respondents, Hanoi City has 60 respondents, Danang City has 50 respondents and Cantho City has 30 respondents. The primary sources of data collected from July 2015 to November 2017 in Vietnam. Simple random sampling technique. The Data analyzed weighted mean. Responses measured through an adapted questionnaire on a 5-point Likert scale. Finally, the findings of the study have the internal factors affecting the competitiveness of the bottled natural mineral water and purified drinking water enterprises with significance level 0.05.